Casos y cosas: semanario popular (Vol. 2, No. 60) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Correo de las brujas, ¡Ha llegado la hora!, Apuntes de un tonto, Por esas calles.

ENGLISH: Includes: Witches' mail, The time has come!, Notes of a fool, Through those streets.
Cases and things: popular weekly magazine (Vol. 2, No. 60)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas